Adult learners' interactional devices of identification and community membership in the EFL classroom (2017)
This research work emerges as a response to the absence of theories that account for the interactional devices of identity construction and affiliation to learning communities, developed by EFL learners in exolingual contexts as Colombia. For this purpose, Conversation Analysis was applied to thirty transcriptions of student-student conversations recorded along a week of class. The study counted with the participation of fifteen students attending a course of basic level at a private non-profit language institute of Bogota in the Adult English Program. From the analysis guided by the principles of Conversation Analysis and Grounded Theory four main interactional devices emerged with linguistic, paralinguistic and metalinguistic properties associated. Thus, the learners construct their positions and affiliative bonds in their language learning community 1) framing questions and propositions as initiating actions, 2) answering or with responding actions, 3) reparing and 4) laughing.